2022
DOI: 10.1038/s41467-022-28725-7
|View full text |Cite
|
Sign up to set email alerts
|

Principles of human movement augmentation and the challenges in making it a reality

Abstract: Augmenting the body with artificial limbs controlled concurrently to one’s natural limbs has long appeared in science fiction, but recent technological and neuroscientific advances have begun to make this possible. By allowing individuals to achieve otherwise impossible actions, movement augmentation could revolutionize medical and industrial applications and profoundly change the way humans interact with the environment. Here, we construct a movement augmentation taxonomy through what is augmented and how it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 119 publications
(222 reference statements)
0
46
0
Order By: Relevance
“…We showed that by closing the loop with a peripheral neural interface based on MU activity, subjects could volitionally modulate the power of cortical β bursts. This could provide new possibilities to exploit cortical β, for example, as a control signal for virtual or robotic effectors ( Dominijanni et al, 2021 ; Eden et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…We showed that by closing the loop with a peripheral neural interface based on MU activity, subjects could volitionally modulate the power of cortical β bursts. This could provide new possibilities to exploit cortical β, for example, as a control signal for virtual or robotic effectors ( Dominijanni et al, 2021 ; Eden et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Possible extracted control signals may depend on behavioural changes and not on a designated descending control command, and therefore, may not satisfy the intended application. Similar constraints effectively apply for augmentation when the aim is to extend the degrees of freedom that a human can volitional control, that is, adding supernumerary degrees of freedom to the natural ones ( Eden et al, 2022 ; Dominijanni et al, 2021 ). In such cases, if the control of a supernumerary degree of freedom is based on single MU activation, this activation must be uncoupled from motor behaviour to ensure coordination between natural and supernumerary effectors.…”
Section: Discussionmentioning
confidence: 99%
“…This would correspond to breaking common input into multiple inputs. Nevertheless, even based on behavioural changes, single MU control can be a resource for specific neural-interface applications, for example, in the absence of any additional motor information or to augment a specific motor task (see Eden et al, 2022 for augmentation by transfer ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are interested in the idea of minimizing physical disabilities of users in the virtual worlds through specially designed virtual avatars 38 . Human movement augmentation such as supernumerary limbs, body-parts remapping, and exoskeletons expands physical abilities both for impaired and unimpaired individuals 39 42 . Virtual co-embodiments like the shared body 7 , 8 and our joint body could expand human collaborations as a co-embodied avatar by combining different persons’ strengths and compensating weaknesses.…”
Section: Discussionmentioning
confidence: 99%